ETNOGRAFI KOMUNIKASI PADA MEDIA PERPESANAN GRUP WHATSAPP “10.CIGASONG MEMBER ONLY” - Pujiyanti, Dini; Ri'aeni, Ida; Risnawati, Ririn (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2022)
Communication is a way for us to be able to understand each other and know what the other means and vice versa. This study aims to find out how to construct and interpret meaning and how to rule in a conversation. Research using an ethnographic approach to communication focuses on studying how members of a cultural group use language (communicate) in social life or social interaction. Hymes argued that communication ethnography is a speech situation, speech event, and speech act. The speech situation itself is defined by Hymes as a set of situations in (or marked by the absence of) speech (situations associated with (or marked by the absence of) speech), (Anshori, 2017). Especially related to speech situations, speech events, and speech acts. Researching the ongoing communication process, analyzing conversations in whatsapp groups, and seeing how speech situations, speech events, and speech acts in conversations on whatsapp group media are 10.CIGASONG MEMBER ONLY. WhatsApp groups are defined as appropriate and effective media in maintaining communication between members. The analysis of the conversations contained in the wahtsapp10.CIGASONG MEMBER ONLY group is also related to the ethnography of communication because of the role of language as a conversational or communication activity. Of course, the utterances analyzed in this study are in the form of conversations in the context of interactions with members of one another in the group. Each member in the WhatsApp group has a different perception or meaning in responding to the content of the message, because each member or person has different thoughts, therefore they must know the situation of speech, speech events, speech acts in an ongoing conversation and the use of paying attention to various languages. need to pay attention to speakers and speech partners, the purpose of the context and speech so that there is no misunderstanding in the use of speech, so as not to cause misunderstanding or miscommunication in the long term. Keywords: Conversation, Ethnography Communication, Speech situations, Speech events, Speech acts.